2001
DOI: 10.1097/00001648-200105000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of Stress and the Common Cold

Abstract: The common cold is one of the major causes of work absenteeism. Former studies, based on artificial inoculation of rhinovirus, implicated psychological stress in the occurrence of this syndrome, either by increasing susceptibility to the virus or by causing the subject to overrate the perception of the symptoms. Nevertheless, few studies on the effect of stress on the naturally acquired common cold have been conducted. We carried out a 1-year prospective cohort study among the faculty and staff of a Spanish un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 19 publications
1
41
1
5
Order By: Relevance
“…Unlike previous research estimating associations of colds and mental health by using self-reports of mental health conditions related to symptom scales [1][2][3][4][5], this study used DSM-IV mental disorder diagnoses that were assessed with a well-established standardized diagnostic interview, administered by trained clinical interviewers. It is also noteworthy that our findings are based on data from a representative population sample, whereas earlier findings about the effect of mental health on the vulnerability to colds mostly relied on results from experimental studies that used subjects fulfilling certain health criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike previous research estimating associations of colds and mental health by using self-reports of mental health conditions related to symptom scales [1][2][3][4][5], this study used DSM-IV mental disorder diagnoses that were assessed with a well-established standardized diagnostic interview, administered by trained clinical interviewers. It is also noteworthy that our findings are based on data from a representative population sample, whereas earlier findings about the effect of mental health on the vulnerability to colds mostly relied on results from experimental studies that used subjects fulfilling certain health criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that poor mental health conditions including perceived stress [1][2][3] and negative mood [2,4,5] are risk factors for developing a common cold. However, prior data relate to symptom scales rather than diagnoses of mental disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential bias is inevitable in any study. Although the subjects were randomized to each group and data were analyzed by considering several factors, the effect of unmeasured factors such as physical and psychologic stress may be important in evaluating the role of vitamin C on the common cold (Hemila, 1996;Takkouche et al, 2001). The findings in this study must be interpreted in light of possible sample selection bias, which may affect the ability to apply our results to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Oftentimes individuals will not seek medical intervention until symptoms becomes more serious or uncomfortable. Using a previously validated disease assessment instrument for the common cold (Takkouche et al, 2001(Takkouche et al, , 2002, our subjects reported a myriad of symptoms on a rated scale. Subjects also had the option of reporting zero symptoms at each weekly reporting period.…”
Section: Effect Of Zinc Supplements On Preventing Upper Respiratory Imentioning
confidence: 99%